Selecting the distinctive points of the land surface for modelling the relief - Stankevičius, Žilvinas (Geodesy and Cartography, 2015)
In order to prepare a project on rebuilding an old or constructing a new road and work drawings, knowledge of the present local objects is necessary. The performance of road construction or reconstruction is aimed at using digital models for the relief and at helping with more precise design, a decrease in the environmental impact and work optimization. Digital local models are most frequently prepared according to data on laser scanning. Redundant metering data on height points have been accumulated using a laser scanning technique. Because of redundant height points, for automatically creating and designing a model for the relief, computer resources must be irrationally used under slower modelling processes. The methodology provided in the article could be suitable for eliminating redundant points of height metering keeping them in distinctive relief positions. According to the proposed methodology, an algorithm has been created and used in the experimental theory for eliminating redundant points. In order to check the correctness of algorithm performance, a project on road reconstruction has been simulated and the volumes of land works using relief models created in the event of the full and filtrated array of height points have been compared.